Disaster readiness of medical records in Malaysian hospitals / Mohd Nizam Yunus - Yunus, Mohd Nizam (2019)
Medical records are an important asset to medical institutions especially hospitals. They document information including patient's identification data, medical and health history, physical examination findings, laboratory results and reports, medical diagnosis, medical treatment, length of stay in hospital, results from medical care and also future course of action. Medical records must be protected from danger or harm as it is vital for the medical institution's operation. There is a need to identify whether medical record is being well safeguarded from any disaster. This study focuses on the readiness of three hospitals in facing disaster on their medical records. Studies were conducted in the Klang Valley area where previous disaster incidents had been reported nearby. Elements of disaster readiness were being constructed from various guidelines and literatures and were being used as a base for interviewing respondents. Data from interviews were analyzed together with findings obtained from literatures and observation at the interview sites. This research suggested that while respondents were aware of the risks that can damage their medical records, some obstacles had hampered their efforts in minimizing or eliminating these risks. While conducting this research, cases of disaster incidents on the existing medical records had been found in all three cases. This shows that incidents had happened before to their medical records. One of the main factors that need to be overcome is the lack of financial support. Hospitals already spent a large amount of money on their manpower, medical operations and medications. An increase of expenditure spent on managing disaster is not possible. It is hope that this study will highlight the importance of a high level of readiness in facing disaster on medical records. To maintain a high level of readiness, various factors are needed including the increase of budget allocation.